THE FAILURE OF COSMOPOLITANISM: THE LAICITE RULES AS A CRISIS OF FRENCH MUSLIMS - Sholihin, Fitri (Hunafa: Jurnal Studia Islamika, 2021)
This paper discusses the increasingly visible failure of cosmopolitanism in France. Laïcité rules are considered as a form of cosmopolitanism that determines between religion and the State, but currently, laïcité are considered as a "tool" to regulate individuals to regulate themselves with certain political, social, and cultural values adjusted by the State. Islam is the second-largest religion after Christians in France, and this makes Islam a debated subject in France. For several ages, the Government issued a policy to restrain Muslim freedom especially women for use hijab, and recently Government ban the use of the niqab in public spaces. In 2020, President Emmanuel Macron issued a plan to stop for the existence of imams and teachers from 9 Islamic countries to prevent separatism and avoid those who disagree with French values. Keywords : Cosmopolitanism, Laïcité, Headscarf Affair Policy, Islam.